Perceived social support from family and friends and bullying victimization among adolescents - Shaheen, Abeer M.; Hamdan, Khaldoun M.; Albqoor, Maha; Othman, Areej Khaleel; Amre, Huda M.; Hazeem, Mohammed Nabeel Abu (Children and youth services review, 2019)
Bullying victimization among adolescents is a major public health concern. Supportive relationships from family and friends can decrease the risk of bullying victimization. To examine differences in perceived social support and to determine predictors of bullying victimization among Jordanian adolescents. This study used a cross-sectional design. Stratified random sampling was used to select a sample of 436 adolescents. Personal Experiences Checklist was used to assess adolescents' bullying victimization and the Perceived Social Support Scale was used to assess adolescents' perceived support from family and friends. Means of support from family and friends were 11.19 (SD = 4.43) and 10.86 (SD = 3.83), respectively. Predictors of bullying victimization were adolescents' age, gender, and father level of education, the use of a computer or other electronic devices, and social support from family. Girls received more support from friends than boys. Adolescents aged 14–16 years received the highest level of social support. Our findings highlight the importance of receiving social support from families and the need for increasing nursing interventions that focus on family-centered care. There is a need for building school programs that enhance group-dynamics among adolescents to improve peers' relationships and help with reducing bullying victimization. What is known on the subject?•Little is known about the importance of supportive peer relations relative to supportive family relations within middle-income countries, which are considered family-centered societies.What does this paper add to existing knowledge?•Although supportive peer and family relations are important during adolescence, adolescents in the current study reported low perceived family and peer social support.•Perceived social support from family significantly predicted lower bullying victimization. However, male adolescents needed more support from family to reduce bullying victimization.•In contrast to some previous research, we found that social support from friends was not a significant predictor of bullying victimization•What are the implications for practice?•Our findings indicate an urgent need to study the determinants of social support among adolescents.